Pengetahuan Tokoh Masyarakat dan Kader Kesehatan Tentang Program Eliminasi Filariasis Limfatik di Kecamatan Pemayung Kabupaten Batanghari Provinsi Jambi - Hotnida Sitorus; Lasbudi P. Ambarita; Maya Arisanti; Helper Sahat Manalu (ASPIRATOR - Journal of Vector-borne Disease Studies, 2016)
Lymphatic filariasis (LF) is a disease caused by filarial worms that until recently was remains a health problem in Indonesia. Jambi province is one of endemic areas for Lymphatic filariasis that some of its regency already implemented mass drug administration (MDA) program. One of regency which has already implemented mass drug administration is Batanghari Regency with 66 chronic cases. Mass drug administration has been started in Batanghari Regency since 2009 and the implementation unit is subdistrict of Pemayung. MDA coverage in the first year is 74,2 percent. The purpose of this research was to determine knowledge of cadres involved in MDA and community leader related to elimination program of Lymphatic filariasis in Pemayung Subdistrict of Batanghari Regency. The results show cadres have good knowledge in regard to the symptoms, impact of disease and prevention aspects. Cadres also support the program of mass drug administration. Knowledge of community leaders show poor on LF disease symptom, but they have good knowledge about the impact of the disease. They also agree and support the implementation of mass drug administration. Cadres and community leaders have experience that the community fear to drink medicines due to side effects of drugs. Conclusion of the research was cadres and community leader has good knowledge regard to the Lymphatic filariasis elimination program.